The Market Reaction to the Announcement of Large-Scale Social Restrictions - I Gede Wahyu Indrawan; I Ketut Yadnyana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Indonesian government implements the PSBB policy, namely large-scale social restrictions. Thus, each industry may experience varying responsiveness depending on how restrictions affect the company and its sector. The sample is 625 companies and the data analysis technique uses one sample t-test and one-sample Wilcoxon sign-test. The results of the analysis show that there was a negative market reaction to the PSBB announcement in all sectors and the information was known to the public before it was announced. PSBB can hamper the business cycle, including hampered supply which results in production delays, low public purchasing power due to decreased sources of income due to activity restrictions. Investors can observe the government's steps in making policies to avoid the risks that may occur. Future research is expected to be able to conduct research using the IDX-IC sector classification.